Developing Culture-Based Tourism Attractions through Pentahelix Collaboration in Satupam Tourism Village - Ellan Jaya Adi Putra; Luisa Cornelia Wijaya; Jessica Natania Vinata; Steven Ryan Tedja; Budi Setiawan (Jurnal Sains Terapan Pariwisata, 2026)
This study analyzes the development of culture-based tourist attractions in Satupam Tourism Village, South Tangerang, by focusing on the implementation of the pentahelix collaboration model. Utilizing a qualitative method with a Participatory Rural Appraisal (PRA) approach, the research involves active collaboration between academics, tourism managers, and local communities. The findings reveal that pentahelix collaboration has been initiated through the academic sector's role in providing legal assistance and human resource training, as well as local government support via a formal Memorandum of Understanding (MoU). A significant cultural transformation is identified within the Rumpun Betawi community, where the "Palang Pintu" performance has evolved from a private traditional ritual into a symbolic attraction for welcoming tourists. Furthermore, while media outlets have begun promoting the village’s potential, the business sector’s involvement remains limited to incidental service usage without long-term investment. The research concludes that integrated synergy among these five pillars serves as a vital strategic foundation for building a sustainable cultural tourism destination. Despite the village being in the preparation phase for general visitors, the internal readiness and collective spirit of local actors indicate strong potential for Satupam to grow as a representative hub for Betawi cultural identity in the region.